Avaliação metodológica do potencial anti-incrustante de moléculas derivadas da d-gluconolactona no cenário de produção de petróleo - Gonçalves, Aline Domingos (2011)
The need of sea water use as displacement fluid in secondary oil recovery at offshore platforms can cause inconvenient such as inorganic scale. This happens due to the mixing between the injection water (sea water), rich in sulfate, and formation water, rich in Ba2+, Ca2+ and Sr2+, causing BaSO4 (or CaSO4 or SrSO4) precipitation. Moreover, changes in temperature and pressure throughout the production process can cause CaCO3 precipitation. An alternative to avoid such problems is the use of chemicals, known as scale inhibitors, which play roles in the nucleation and crystal growth stages. Efforts have been made in finding new substances that are environmentally friendly, or that have multiple functions (eg: scale inhibitor and H2S scavenger), classified as combo or multifunctional products. In this context, this work aims to optimize a methodology to evaluate new products which are candidates for inhibition of barium sulfate and calcium carbonate precipitation. Gluconamides, derived from the carbohydrate Dgluconolactone, were specifically studied, due to the presence of hydroxyl groups in its composition, able to capture metals in solution, which could prevent the formation of precipitates. The steps of the methodology include solubility study and determination of the molecule dissociation constant(s). Nephelometry and turbidimetry techniques were applied to monitor the turbidity of the solutions and identify the critical supersaturation ratio. Static tests of inhibition efficiency were conducted and the evaluation of the molecules s anti-fouling action was done by measuring the remaining cation in solution, using the ICPMS or FAAS techniques. For comparison a commercial inhibitors were used. The influence of variables such as pH, temperature, ionic strength and time on the performance of the molecules was also studied.